2012
DOI: 10.1590/s1516-14392012005000089
|View full text |Cite
|
Sign up to set email alerts
|

Nanocomposites of polyamide 6/residual monomer with organic-modified montmorillonite and their nanofibers produced by electrospinning

Abstract: Nanocomposites of an organic-modified montmorillonite (MMT) and polyamide 6 (PA6) with a residual monomer were produced by melt mixing in a torque rheometer. By wide angle X-rays diffraction (WAXD), intercalated/exfoliated structures were observed in the PA6/MMT nanocomposites with 3 and 5 wt. (%) of MMT; on the other hand, when 7 wt. (%) of MMT was added, a nanocomposite with exfoliated structures was obtained due to the predominant linking reactions between the residual monomer and the "nanoclays" organic su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 15 publications
0
12
0
1
Order By: Relevance
“…These results indicate that the high elongational forces developed during the electrospinning process changed the initial intercalated/exfoliated structure of the nanocomposites to an exfoliated one [112].…”
Section: Properties and Potential Applicationsmentioning
confidence: 85%
See 1 more Smart Citation
“…These results indicate that the high elongational forces developed during the electrospinning process changed the initial intercalated/exfoliated structure of the nanocomposites to an exfoliated one [112].…”
Section: Properties and Potential Applicationsmentioning
confidence: 85%
“…Nanocomposites of an organic-modified MMT and PA6 with a residual monomer were once produced by melt blending in a torque rheometer [112]. By WAXD, intercalated structures were observed in the nanocomposites with 3 and 5 wt% of MMT; on the other hand, when 7 wt% of MMT was added, an exfoliated structure was obtained due to the predominant linking reactions between the residual monomer and the polar organic surfactant.…”
Section: Properties and Potential Applicationsmentioning
confidence: 99%
“…Polyamides are semicrystalline polymers and the presence of peak broadening indicates the existence of amorphous regions. Furthermore, the introduction of clay, regardless of the amount, changes slightly the shape and intensity of the peaks at 20º and 24º of the polyamide6 [30][31][32][33][34][35] . It was found that the addition of 5% w/w of MMT in PA6, cause the appearance of the new reflection at 2θ = From Figure 2, it is noted that the general profile of FTIR spectra of the PA6 remained virtually unchanged, except for a small increase in the intensity of the peaks at wavelengths of 800, 1033 and 1095 cm -1 .…”
Section: Water Permeability and Oil Retentionmentioning
confidence: 94%
“…A method for obtaining a nanocomposite based on PP/PA-6 mixture with increased physico-mechanical characteristics, using the positive effect of PVP for obtaining a homogeneous mixture [10] and MMT for increasing the strength characteristics of the composite is proposed [15,16]. At first nanocomposite based on PA-6 with MMT, which is intercalated with polyvinylpyrrolidone is synthesized.…”
Section: Polyvinylpyrrolidonementioning
confidence: 99%